Big Meg: The Story of the Largest and Most Mysterious Predator That Ever Lived : The Story of the Largest and Most Mysterious Predator That Ever Lived - Flannery, Tim F., (Tim Fridtjof), 1956-; Flannery, Emma (New York : Atlantic Monthly Press, 2024)
"Internationally bestselling author and renowned scientist Tim Flannery and his daughter, scientist Emma Flannery, deliver an informative-yet-intimate portrait of the megalodon, an extinct shark and the largest predator of all time. When Tim Flannery was a boy he found a fossilized tooth of the giant shark megalodon at a beach near his home in Australia. This remarkable find-the tooth was large enough to cover his palm-sparked an interest in paleontology that was to inform his life's work and a lifelong quest to uncover the secrets of the great shark Otodus megalodon. Tim passed on his love of the natural world and interest in the fossil record to his daughter, Emma, a scientist and writer. And now, together, they have written a fascinating account of this ancient marine creature. Big Meg charts the evolution of megalodon, its super-predator status for about fifteen million years and its decline and extinction. It delves into the fossil record to answer questions about its behavior and role in shaping marine ecosystems as well as its impact on the human psyche. It contains stories of the scientist and amateur fossil hunters who have scoured the seas, and land, for fossil remains, drawn to the beauty and mystique of the great shark, sometimes meeting their death in the process. Deemed "in the league of the all-time great explorers" by David Attenborough, Tim Flannery has come together with Emma Flannery to spin a story of the great natural history of our planet as enthralling as the fossil record itself"--.
"First published in Australia in 2023 by the Text Publishing Company"-- CIP galley.
Includes bibliographical references and index.
Keywords: Carcharocles megalodon; Animals, Fossil; Marine Life; Dinosaurs & Prehistoric Creatures